Exploring the Creative Process: Integrating Psychometric and Eye-Tracking Approaches - Jankowska, Dorota M.; Czerwonka, Marta; Lebuda, Izabela; Karwowski, Maciej (Frontiers in Psychology, 2018)
This exploratory study aims at integrating the psychometric approach to studying creativity with an eye-tracking methodology and thinking-aloud protocols to potentially untangle the nuances of the creative process. Wearing eye-tracking glasses, one hundred adults solved a drawing creativity test – The Test of Creative Thinking-Drawing Production (TCT-DP) – and provided spontaneous comments during this process. Indices of visual activity collected during the eye-tracking phase explained a substantial amount of variance in psychometric scores obtained in the test. More importantly, however, clear signs of methodological synergy were observed when all three sources (psychometrics, eye-tracking, and coded thinking-aloud statements) were integrated. The findings illustrate benefits of using a blended methodology for a more insightful analysis of creative processes, including creative learning and creative problem-solving.